A case of cerebrotendinous xanthomatosis. II: The sterol content of a cataractous lens. Issue 10 (October 1990) - McKenna, P.; Morgan, S. J.; Bosanquet, R. C.; Laker, M. F.
Abstract : The cholestanol content of a cataractous lens nucleus from a patient with cerebrotendinous xanthomatosis (CTX) was quantified by gas chromatography-mass spectrometry and found to be 0.27 micrograms per mg freeze-dried lens tissue. The cholestanol-cholesterol ratio of 1.7% in the lens nucleus was similar to that in the serum of the CTX patient. The cholestanol content and cholestanol-cholesterol ratio in the CTX lens were approximately four-fold and six-fold greater respectively than the mean levels found in three senile cataractous lens nuclei analysed simultaneously for comparative purposes.